2015
DOI: 10.1080/19476337.2014.992967
|View full text |Cite
|
Sign up to set email alerts
|

DNA scission inhibition, antioxidant, and antiproliferative activities of water chestnut (Trapa natans) extracted in different solvents

Abstract: This investigation deals with the study of polyphenolic, antioxidant, and antiproliferative activities of water chestnut extracted in different solvents. The antioxidant activities of the extract in different solvents were the maximum in methanol, followed by ethanol and aqueous solution and were found to be 39.8%, 34.1% and 32.6% from DPPH assay, and 45.64%, 35.08% and 30.52% from lipid peroxidation assay, respectively, whereas the reducing power inhibition assay showed the maximum antioxidant potential in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Effect of mushroom extracts on cell viability Antioxidants are known to restrain cell proliferation and apoptosis, which depends on the nature of antioxidants, types of tumor cells, and treatment program (43)(44)(45). The present study showed that all the mushroom varieties possess antiproliferative activity against Colo-205 and MCF7, as shown in Fig.…”
supporting
confidence: 55%
“…Effect of mushroom extracts on cell viability Antioxidants are known to restrain cell proliferation and apoptosis, which depends on the nature of antioxidants, types of tumor cells, and treatment program (43)(44)(45). The present study showed that all the mushroom varieties possess antiproliferative activity against Colo-205 and MCF7, as shown in Fig.…”
supporting
confidence: 55%
“…The total phenolic content (TPC) of walnut extracts were determined using the Folin–Ciocalteu reagent method (Gani et al . ) with certain modifications. The sample extract (100 µL) was added to 1.5 mL of freshly prepared Folin–Ciocalteu reagent (1:10 v/v with water).…”
Section: Methodsmentioning
confidence: 99%
“…The percent inhibition of black and green tea at a concentration of 20 µg/ml was 9.7% and 10.1% which increased to 48.06% and 56.06% at 100 µg/ml, respectively, which is less than that of BHT (67.76%), the known standard at the same concentration. Gani et al [18] reported that inhibition of lipid peroxidation may be associated with the presence of phenolics in the extract.…”
Section: Lipid Peroxidationmentioning
confidence: 98%
“…Total phenolic content was determined based on the method described by Gani et al [18] with some Eppendoff) at 37°C in 5% CO 2 with 98% relative humidity. Cells were allowed to adhere and grow for 24 h in culture medium before exposure to extract.…”
Section: Total Phenolic Contentmentioning
confidence: 99%